2023
DOI: 10.3390/molecules28052012
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis Reveals the Mechanisms of Sinapine Alleviate Macrophage Foaming

Abstract: Rapeseed polyphenols have cardiovascular protective effects. Sinapine, one main rapeseed polyphenol, possesses antioxidative, anti-inflammatory, and antitumor properties. However, no research has been published about the role of sinapine in alleviating macrophage foaming. This study aimed to reveal the macrophage foaming alleviation mechanism of sinapine by applying quantitative proteomics and bioinformatics analyses. A new approach was developed to retrieve sinapine from rapeseed meals by using hot-alcohol-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The enhancement of antioxidant protection can also be ascribed to the fermentation process, which enriches rapeseed meal with bioactive compounds like vitamins, enzymes, polysaccharides, and additional polyphenols. A significant phenolic component in rapeseed meal is sinapine, which accounts for up to 80% of all phenols and is known for its robust antioxidant properties (Liu et al, 2023). The mechanism of polyphenols in antioxidative defense primarily involves scavenging reactive oxygen species, such as hydroxyl and superoxide radicals (Zhao et al, 2021), and chelating transition metal ions like Fe +2 , which are known to generate free oxygen radicals (Taranu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of antioxidant protection can also be ascribed to the fermentation process, which enriches rapeseed meal with bioactive compounds like vitamins, enzymes, polysaccharides, and additional polyphenols. A significant phenolic component in rapeseed meal is sinapine, which accounts for up to 80% of all phenols and is known for its robust antioxidant properties (Liu et al, 2023). The mechanism of polyphenols in antioxidative defense primarily involves scavenging reactive oxygen species, such as hydroxyl and superoxide radicals (Zhao et al, 2021), and chelating transition metal ions like Fe +2 , which are known to generate free oxygen radicals (Taranu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanations were as follows: (1) CDC42 inhibited atherosclerosis and relieved coronary artery stenosis, thus decreasing the accumulating TLF rate [ 21 , 22 ]. (2) CDC42 not only reduced the accumulating TLF rate, but also balanced blood lipid levels and reduced inflammation, thereby further reducing the accumulating MACE rate in DCB-treated SV-CAD patients [ 25 , 27 ]. Furthermore, our study showed that CDC42 at D7 independently predicted TLF and MACE rates in DCB-treated SV-CAD patients.…”
Section: Discussionmentioning
confidence: 99%